Determinan Tingkat Kemiskinan di Karesidenan Madiun Dengan Data Panel - Novia Atina Titania; Eni Setyowati (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Poverty has become a multidimensional and complex problem. Therefore, it is necessary to make efforts to eradicate poverty that are carried out in an appropriate and targeted manner. The purpose of this research is to analyze the influence of Regency Minimum Wage, Human Development Index, Gini Ratio, and Percapita Income on Poverty Level in Madiun Residency. This study uses secondary data in the form of panel data, which means a combination of cross sectional and time series data. Sources of data obtained from the Central Bureau of Statistics and the Department of Manpower and Transmigration of East Java Province. The dependent variable in this study is the poverty level of the district/city in the Madiun residential area in 2016-2020. The independent variables are the Regency Minimum Wage, Human Development Index, Gini Ratio and Per capita Income. The results showed that there was no influence of the Regency Minimum Wage and Gini Ratio on the poverty level. On the other hand, there is an influence of Human Development Index and Per capita Income on poverty levels.